Landscape across dam at Dobikin, Moree, New South Wales, ca. 1970 - Stacey, Wes (Wesley), 1941-2023. (1968)
Depicting dam, flat paddocks, distant horizon.
Part of the Wes Stacey archive of architectural photographs, 1968-1972.
Catalogue record generated as part of a batch load.
Title from acquisitions documentation, see file NLA09/703.
Wes Stacey reference number: 5 26 4.
Also available online
Keywords: Dams -- New South Wales -- Dobikin -- Photographs; Dobikin (N.S.W.) -- Photographs